Papillary carcinoma in a thyroglossal duct: case report - Martins, Antonio Santos (1999)
CONTEXT: Thyroglossal duct cysts are the most common congenital cervical abnormality in childhood. Malignant lesions are rare in thyroglossal duct cysts (about 1%). OBJECTIVE: To report a case of papillary carcinoma in thyroglossal duct cysts. DESIGN: Case report. CASE REPORT: The patient was a 21-year-old female with a four-month history of an anterior midline neck mass but without other symptoms. The physical examination revealed a 4.0 cm diameter, smooth, painless, cystic nodule at the level of the hyoid bone. The thyroid gland was normal by palpation and no neck lymph nodes were found. Indirect laryngoscopy, fine-needle biopsy aspiration and cervical ultrasound were normal and compatible with the physical findings of a thyroglossal duct cyst. The patient underwent surgery with this diagnosis, under general anesthesia, and the mass was resected by the usual Sistrunk procedure. There were no local signs of invasion of the tissue surrounding the cyst or duct at surgery. The patient was discharged within 24 hours. Histopathological examination of the specimen showed a 3.5 x 3.0 x 3.0 cm thyroglossal cyst, partially filled by a solid 1.0 x 0.5 cm brownish tissue. Histological sections showed a papillary carcinoma in the thyroid tissue of a thyroglossal cyst, with normal thyroid tissue at the boundary of the carcinoma. There was no capsule invasion and the margins were negative. The follow-up of the patient consisted of head and neck examinations, ultrasonography of the surgical region and thyroid, and total body scintigraphy. The patient has been followed up for two years with no further evidence of disease.